Assessment of Nurses` Practice Regarding Poisoning Children - Saeed Kadhim, Nuha (Iraqi National Journal of Nursing Specialties, 2022)
Objectives: Assess nurses` practices for children with chemical poisoning, and find out relationship between nurses` socio- demographic data and their practices for children with chemical poisoning.Methodology: A descriptive correlational design used to achieve the purpose of the study, the study was conducted at Al-Basrah Hospital for Maternal and Children throughout the period 12th of September 2021 to 10th of October 2022. A non- probability sample of (30) nurse at emergency department was selected. The instrument of the study was constructed based on previous literatures that related to study project, which include nurses` socio-demographic data and questionnaire format to assess nurses` practices about children with chemical poisoning. The data was collected by self-administered method and analyzed by SPSS program version 20.Results: The findings of the study showed the mean of nurses` practices assessment scored (≤1.66), 56.7% of them has diploma in nursing, 86.7% with no training courses about poisoning first aids, and more than half of them have less than 5 years of experience.Conclusions: Nurses`Practices for children with chemical poisoning were inadequate, there was no association between nurses` sociodemographic data and their practices except their years of works at hospital.Recommendations: Encourage nurses to update their knowledge and practice regarding management of poison children through training courses, use standardized guideline for poisoning care.